ChemInform Abstract: Palladium‐Catalyzed Intramolecular Insertion of Alkenes into the Carbon—Nitrogen Bond of β‐Lactams. Issue 2 (23rd December 2015) - Yada, Akira; Okajima, Satoshi; Murakami, Masahiro
Abstract: The title reaction proceeds via cleavage of the C—N bond of β‐lactams (I) and (III) by Pd(0) followed by intramolecular alkene insertion.